Credit Risk Control Strategi By Implementing US' Index Theory In Reducing Non-Performing Loans Within Banking Industry and Financial Institution Sector - Amir Chan, Eriza; MMP Siahaan, Uke (The Indonesian Journal of Business Administration, 2016)
Abstract - The economic crisis has been decreased the performance of Banking Industry in Indonesia as reflected in the decreasing of Loan Growth and the increasing of Non-Performing Loans (NPLs) ratio since 2015. Increasing NPLs was followed by increasing cost of loan and decreasing ROA of Banks and others financial institutions therefore Bank should be innovate to enhance its loan quality. This study was conducted to determine influence of leverage towards profitability ratios of 68 companies which are debtors of Bank ABC in Performing Loan quality within two groups of US' Index value and tested by Correlation Statistic. Based on the research’s outputs, it was concluded that in group of US’ Index < 1 leverage has been influencing negatively to its profitability while on another group, with US’ Index > 1, leverage has been influencing positively. Those conclusions were reinforced by the decline trend of US 'Index value on financial performances of 21 debtors were included in the category of watch-list debtors as well as proven in the study case of debtor which is now included into the category of non-performing loans. This study has shown that US’ Index theory could be implemented in all stages of loan process, such as to analysis the repayment capacity of applicants at the front end, as loan monitoring system at  the middle end, and as a guidance in loan restructuring and collecting repayment at  the back end stage. Therefore, this study suggests the use of US’ Index theory as a credit risk control strategy to reducing NPLs in Banks and Financial Institutions in order to enhance its loan quality and generate sustainable profit. Key words: NPLs, Cost of Loan, US’ Index, Capital Structure, Correlation Statistic.